Validation of the Tunisian Empathy Scale for Children (TESC) in General Population and Children With Autism Spectrum Disorder - Ben Youssef, Hela; Halayem, Soumeyya; Ghazzai, Malek; Jelili, Selima; Ben Mansour, Hager; Rajhi, Olfa; Taamallah, Amal; Ennaifer, Selima; Hajri, Malek; Abbes, Zeineb Salma; Fakhfakh, Radhouane; Nabli, Ahmed; et al. (Frontiers in Psychiatry, 2022)
Background: Several empathy assessment tests have been proposed worldwide but none of them took into account cultural variations that seem to affect empathic manifestations. The aim of this study was to create and validate an empathy assessment questionnaire for school-aged Tunisian children entitled "Tunisian Empathy Scale for Children" (TESC). Methods: An evaluative cross-sectional study was conducted. The questionnaire was administered to parents of 197 neuro-typical children and 31 children with autism without associated intellectual deficits, aged between 7 and 12 years. Validation steps included: face validity, content validity, construct validity, and reliability study. A ROC curve analysis was used to investigate the diagnostic performance of the TESC. Results: Face validity was verified with an expert panel. Content validity was examined, and 11 items were removed as irrelevant or not assessable by parents. Exploratory factor analysis extracted four domains that explained 43% of the total variance. All these domains were significantly correlated with the total score (p<10-3) and are respectively: empathic behaviors, affective empathy, cognitive empathy, and a combined affective and cognitive domain. The reliability study showed a satisfactory level of internal consistency of the TESC, with a Cronbach's alpha of 0.615. The diagnostic performance of the TESC in relation to autism was evaluated by the ROC curve with a sensitivity and specificity of 84.3% and 62.1% respectively for a total score of 16. Conclusion: A 15-item questionnaire assessing empathy in a multidimensional and culturally adapted way was obtained. The psychometric qualities of the TESC were satisfactory.